If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3d-2)=32
We simplify the equation to the form, which is simple to understand
4(3d-2)=32
Reorder the terms in parentheses
+(+12d-8)=32
Remove unnecessary parentheses
+12d-8=+32
We move all terms containing d to the left and all other terms to the right.
+12d=+32+8
We simplify left and right side of the equation.
+12d=+40
We divide both sides of the equation by 12 to get d.
d=3.3333333333333
| x^2+2x-52=0 | | -6(5+3x)=14 | | cos(6x)=cos(4x) | | 14.2=0.4(20m-7.8) | | 24+9=21 | | 24+9= | | a+4b=6 | | 12(2e+3)=96 | | -4z-5=8z+3 | | C=20n+8 | | (2z+9)(7-z)=0 | | f(x)=-8x^2+8x+9 | | y=x^2ln(3x) | | n+33=25 | | y=3*(-3)+10 | | -7r=7(8+3r) | | 5ksquared=180 | | x^2+4x-20y+50=0 | | 7t-8=7+t | | m-48=-18 | | -x+7=-26+2x | | 3.92*1000000000000= | | (x-2)[2x-2(3+x)]-12= | | x^3+8x^2+19x+12=0 | | x+5*(3x+10)=2 | | s^3+8s^2+19s+12=0 | | 5+49x=28x+32 | | 1.68*100000000= | | 6a(-2a+3)= | | 6m-1=-4+5m | | (-x+9)(-8-11x)=0 | | z+16=33 |